Effect of Paricalcitol on Bone Density After Kidney Transplantation: Analysis of 2 Transplant Centers (Iranian Journal of Kidney Diseases, 2017)
Introduction. The Kidney Disease: Improving Global Outcomes Clinical Practice Guidelines on the management of bone disease in patients with chronic kidney disease recommend periodic measurement of serum calcium, phosphorus, vitamin D, and parathyroid hormone levels after kidney transplantation, with the frequencies that will vary according to the severity of bone disease and graft function. Paricalcitol, a selective vitamin D receptor activator, is indicated in the prevention and treatment of secondary hyperparathyroidism. Material and Methods. We retrospectively evaluated the effect of treatment with paricalcitol among our kidney transplant recipients. We monitored the effect of paricalcitol on bone density; the plasma levels of parathyroid hormone, calcium, and phosphorus; and proteinuria and calciuria. Comparisons were made between these parameters before treatment and 12 months after treatment. Results. Eighty-eight kidney transplant recipients with a mean age at the time of transplantation of 47.1 ± 10.5 years were receiving paricalcitol. On average, paricalcitol was included into the treatment for 48 months from transplantation (median, 27 months). The patients had significantly improved bone density (P < .001), significantly lower parathyroid hormone levels (P < .001), and significantly decreased proteinuria (P = .02) after 12 months of treatment. During the treatment with paricalcitol, the immunosuppressive therapy, dose of prednisone, body mass index, and vitamin D levels had not significantly changed. Nor had any significant change occurred to graft function. Conclusions. Paricalcitol is an effective therapy for secondary hyperparathyroidism in kidney transplant recipients.